1997
DOI: 10.1097/00019442-199721520-00002
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Replacement and Response to Fluoxetine in a Multicenter Geriatric Depression Trial

Abstract: The estrogen decrease of the postmenopausal state may be a factor in both the pathogenesis of late-life depression and in therapeutic response. Studies of nondepressed women over 60 given estrogen replacement therapy (ERT) suggest improvement in mood. The authors compared clinical response of elderly depressed women outpatients entering a 6-week, randomized, placebo-controlled, double-blind, multicenter trial of fluoxetine (20 mg/day); 72 patients received ERT, and 286 did not. There was a significant interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0
6

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(76 citation statements)
references
References 0 publications
1
69
0
6
Order By: Relevance
“…Some studies have investigated the possible effect of estrogen as an adjunct treatment for postmenopausal depression. Whereas an early small study failed to show any benefit when CEE was added to the tricyclic antidepressant imipramine in pre-and post-menopausal women with major depression [157], subsequent reports have suggested that the antidepressant effect of SSRIs may be improved by concurrent estrogen treatment [158][159][160][161]. One retrospective non-controlled study did not reproduce this finding.…”
Section: The Use Of Hormonal Therapies In Clinical Practicementioning
confidence: 99%
“…Some studies have investigated the possible effect of estrogen as an adjunct treatment for postmenopausal depression. Whereas an early small study failed to show any benefit when CEE was added to the tricyclic antidepressant imipramine in pre-and post-menopausal women with major depression [157], subsequent reports have suggested that the antidepressant effect of SSRIs may be improved by concurrent estrogen treatment [158][159][160][161]. One retrospective non-controlled study did not reproduce this finding.…”
Section: The Use Of Hormonal Therapies In Clinical Practicementioning
confidence: 99%
“…Administration of estrogen to PMW for several weeks has also been found to increase cortical serotonin-2A receptors (Kugaya et al, 2003). PMW taking estrogen have improved clinical responses to serotoninergic antidepressants (Nagata et al, 2005;Rasgon et al, 2007;Schneider et al, 1993;Soares et al, 2003b).…”
Section: Introductionmentioning
confidence: 99%
“…The different formulations of estrogen appear to benefit aspects of CNS function in various animal models (Gibbs, 2000;Wise et al, 2001;Bethea et al, 2002a) and in a few clinical studies (Schneider et al, 1997;Roof and Hall, 2000;Schmidt et al, 2000;Newhouse et al, 2002). However, recent reports have indicated that any formulation of HRT increases peripheral cancer risk (Chlebowski et al, 2003;Kerlikowske et al, 2003).…”
Section: Introductionmentioning
confidence: 99%